ANALISIS PERBUATAN OBSTRUCTION OF JUSTICE & PENYELEWANGAN NILAI PANCASILA YANG DILAKUKAN APARAT KEPOLISIAN: (Studi Kasus Ferdi Sambo & Brigadir J) - Ida Arodatul Jannah (The Republic : Journal of Constitutional Law, 2024)
The governor the case regarding Obstruction of Justice became a hot topic of conversation among the people. Now, problems related to law enforcement officials, namely the police, continue to be in the public spotlight and make people wonder what the role and law enforcement is, which is one of the offenses in the occurrence of Obstruction of Justice in premeditated murder cases, and what is the relationship between police rules and police officers? others who also investigated Obstruction of Justice's actions in this premeditated murder case. The purpose of this paper is to analyze and find out whether there are problems with the disappearance of evidence in cases of premeditated murder committed by elements of the police which ultimately lead to Obstruction of Justice. The results of this paper emphasize that there is a need for firmness in applying criminal sanctions to enforce police officers who commit Obstruction of Justice in the article on premeditated murder.